Collaborative Adaptive Learning Model with a Communication Competency Approach during the Covid-19 Pandemic in Indonesia and Japan - Erliany Syaodih; Dasrun Hidayat; Haslina Halim; Leili Kurnia Gustini; Sukatno Krisbianto (STAI Hubbulwathan Duri, 2022)
Indonesia and Japan are among the countries affected by the COVID-19 pandemic. Education in the two countries relies on digital technology so learning is done online. This situation is interesting to study because this is the first time massive online learning has been implemented. The options are either studying online or picking up death. However, online learning of course must be well prepared so as not to leave a bad impact on students. The purpose of this study was to compare students' experiences during online learning during the pandemic between Indonesia and Japan. This research uses a phenomenological study with a qualitative approach. Data collection techniques were through interviews with 30 college students as informants consisting of several universities in Indonesia and Japan. The results of this study are that Indonesian students still experience synchronous and asynchronous obstacles, consisting of technical and non-technical obstacles. Technically with regard to internet networks. Meanwhile, non-technical means that students are not ready to follow online learning so assistance is needed. Students in Indonesia also need time to adapt to using technology. Meanwhile, online learning in Japan has no obstacles. Even online situations are designed to be like classroom learning environments. Lecturers apply a collaborative adaptive learning model by prioritizing an adaptation approach to situations. Adaptation is categorized as one of the aspects of online communication competence which is considered as a success factor in online learning in Japan.